Behavioral Characterization of Electric Vehicle Charging Loads in a Distribution Power Grid through Modeling of Battery Chargers - Ahmed Mohamed, Ahmed Haidar; Muttaqi, Kashem M (2014)
Plug-in Electric Vehicle (PEV) is a new atypical load in power systems. In future, PEV load will play a significant role in the distribution grids. This integrated load into the power grid may overload the system components, increase power losses and may violate system constraints. Currently, the most common method of Electric Vehicle (EV) modeling is to consider the EV loads as constant power elements without considering the voltage dependency of EV charging system during state of charges (SOC). EV load demand cannot be considered as a constant power, as modeling as a constant power load will not provide accurate information about the behavior of charging system during charging process. As several research projects on smart grids are now looking into realistic models representing the realistic behavior of an EV loads, this paper proposes a methodology for modeling of EV charger integrated to an electricity grid in order to understand the impacts of EV charging load. A charging system was designed to capture the EV load behavior and extract the coefficients of the EV ZIP load model. A comparative study was carried out with different types of load models. The results indicate that the assumptions of load demand as a constant power to analysis the effect of PEVs on power grid would not be effective in real time application of PEVs.